2017
DOI: 10.1037/neu0000357
|View full text |Cite
|
Sign up to set email alerts
|

Phonological ambiguity modulates resolution of semantic ambiguity during reading: An fMRI study of Hebrew.

Abstract: Altogether these results are consistent with the prominent role of phonological processing in visual word recognition. Finally, despite differences in hemispheric asymmetry between homophones and heterophones, ambiguity resolution, even toward the subordinate meaning, is largely left lateralized. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 106 publications
(264 reference statements)
1
8
0
Order By: Relevance
“…Moreover, given that the acronyms we used were orthographically legal, these results highlight the role phonology plays not only in the recognition of acronyms, but also in the recognition of regular words. Such results replicate and extend previous studies in Hebrew that investigated the role phonology plays in the extraction of meaning from print by comparing the disambiguation process of two types of Hebrew homographs: homophonic homographs in which both meanings have the same sounds, and heterophonic homographs in which the two meanings have different sounds (e.g., Bitan, Kaftori, Meiri‐Leib, Eviatar, & Peleg, ; Peleg & Eviatar, , ; Peleg, Markus, & Eviatar, ). These studies have repeatedly shown that heterophonic homographs (which are phonologically ambiguous) are processed differently than homophonic homographs (which are phonologically unambiguous).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, given that the acronyms we used were orthographically legal, these results highlight the role phonology plays not only in the recognition of acronyms, but also in the recognition of regular words. Such results replicate and extend previous studies in Hebrew that investigated the role phonology plays in the extraction of meaning from print by comparing the disambiguation process of two types of Hebrew homographs: homophonic homographs in which both meanings have the same sounds, and heterophonic homographs in which the two meanings have different sounds (e.g., Bitan, Kaftori, Meiri‐Leib, Eviatar, & Peleg, ; Peleg & Eviatar, , ; Peleg, Markus, & Eviatar, ). These studies have repeatedly shown that heterophonic homographs (which are phonologically ambiguous) are processed differently than homophonic homographs (which are phonologically unambiguous).…”
Section: Discussionsupporting
confidence: 86%
“…For instance, developmental studies indicate that children's reading development can be predicted by their phonological abilities [87,99]. Evidence of the influence of phonology on adults' reading has also been reported [89,[100][101][102][103][104][105]. As pointed out by Perrone-Bertolotti et al [106], silent reading often involves an imagery speech component: we hear our own "inner voice" while reading.…”
Section: The Indirect Route From Orthography Via Phonology Tomentioning
confidence: 95%
“…Nevertheless, for the present data, no less than 73% of the pseudowords have all their FBS features present. It is only for 2.3% of the pseudowords that more than five FBS features are missing in C For visual word recognition, Baayen et al (2019) found that a dual-route setup, with a direct route straight from orthographic vectors to semantic vectors, and an indirect route going from orthographic vectors to triphone vectors and from the triphone vectors to the semantic vectors, afforded greater precision (see Wong and Chen, 1999;Perrone-Bertolotti et al, 2012;Newman et al, 2012;Jared, Ashby, Agauas, & Levy, 2016;Bitan, Kaftory, Meiri-Leib, Eviatar, & Peleg, 2017;Jared & O'Donnell, 2017;Amenta et al, 2017, for detailed discussion of dual routes in reading). This result led us to inquire whether a second, indirect route, would also enhance model performance for auditory comprehension.…”
Section: From Pseudowords' Transcriptions To Pseudowords' Formsmentioning
confidence: 99%